2012
DOI: 10.3102/0162373712454326
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude, Destinations, and Determinants of Mathematics and Science Teacher Turnover

Abstract: This study examines the magnitude, destinations, and determinants of the departures of mathematics and science teachers from public schools. The data are from the National Center for Education Statistics' nationally representative Schools and Staffing Survey and its longitudinal supplement, the Teacher Follow-up Survey. Our analyses show that rates of mathematics and science teacher turnover, both those moving between schools and those leaving teaching altogether, have increased over the past two decades, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(106 citation statements)
references
References 49 publications
2
103
0
1
Order By: Relevance
“…However, even though science teachers' understanding and appreciation of the culture of students is important, Ingersoll and May () report science teachers often migrate from urban to suburban districts because of greater salaries and fewer discipline problems. This is important because we need to recognize that even though this project is effective in helping our Noyce Scholars make an experience‐based decision about becoming a high‐need NYC science teacher, we have to be concerned that they too will migrate back to suburban non‐high‐need districts after completing their four years of required high‐need teaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though science teachers' understanding and appreciation of the culture of students is important, Ingersoll and May () report science teachers often migrate from urban to suburban districts because of greater salaries and fewer discipline problems. This is important because we need to recognize that even though this project is effective in helping our Noyce Scholars make an experience‐based decision about becoming a high‐need NYC science teacher, we have to be concerned that they too will migrate back to suburban non‐high‐need districts after completing their four years of required high‐need teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, across the teacher retention literature, teachers who perceive that they have more autonomy over their work and higher levels of administrative support are less likely to move to another school or leave the profession (Borman & Dowling, 2008;Guarino et al, 2006;Podolsky et al, 2016Urick, 2016. For example, when organizational characteristics such as principal leadership and teacher autonomy were included in models of mathematics and science teacher turnover, many of the demographic variables, such as poverty rate and locale, that previously predicted turnover, were no longer significant (Ingersoll & May, 2012).…”
Section: The Teacher Workforce and Teacher Turnovermentioning
confidence: 99%
“…Commitment to teaching is vital to reducing teacher turnover, implementing curricular innovations, enacting change within a discipline, maintaining program continuity, sustained success, and enhancing the depth of student development (Firestone & Pennell, 1993;Hausman & Goldring, 2001;Ingersoll & May, 2010;Robinson & Edwards, 2012). Research has identified a noteworthy range of variables which influence commitment to teaching (e.g., classroom management, curriculum delivery competence, work-life balance, and classroom organization issues), highlighting the need for research exploring the relationship between multiple competence areas and commitment to teaching (McKim & Velez, 2016;Mee & Haverback, 2014;.…”
Section: Commitment To Teachingmentioning
confidence: 99%